Analisis Pelayanan Jasa Angkut Barang Kapal melalui Tol Laut dalam Mendukung Pertumbuhan Ekonomi Negara - Kristian Cahyandi; Andi Hendrawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2023)
The Sea Highway Program is intermodal connectivity rather than just providing ports and ships. This research was conducted to analyze how the Sea Highway ship freight services have been effective in supporting the country's economic growth. There have been many studies regarding the geographical location of Indonesia, which consists of thousands of islands, which can be an obstacle to justice and economic prosperity. This research examines from the perspective of providing infrastructure and regulations in facilitating the Sea Highway program. This study uses a qualitative descriptive method with a detailed description of the influence of the maritime program on inter-island logistics distribution. Data collection was done by interview, observation, and literature study. The conclusion obtained is that the Sea Highway Program has become a necessity to expedite the flow of goods and equitable distribution. The community is more interested in using the services of a pertis ship (Sea Highway) because it can load goods in large quantities, making it more effective and efficient.